(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The text goes through three distinct experiences (as spectator, performer and researcher) with scenic manifestations of performative nature in the urban space. In dialogue with the reports, the text exposes various approaches to spatial aspects that involve the urban performative theatrical event, proposes the outline of a certain cartography of the pedestrian-spectator and reflects on the resulting reading of the relationship that street spectacles establish with their audience.